Diversity of culturable endophytic fungi associated with bryophytes, pteridophytes and spermatophytes from Dawei Mountain Nature Reserve, China - Yong-Han Gao (Science Faculty of Chiang Mai University, 2019)
Bryophytes, pteridophytes and spermatophytes are each plants with different evolutionary degrees. In the present study, the diversity and community structure of culturable endophytic fungi (EF) associated with bryophytes, pteridophytes and spermatophytes collected from Dawei Mountain in China were investigated. A total of 2230 EF were isolated from 1440 segments of nine plant species. The colonization rate (CR) of bryophytes, pteridophytes and spermatophytes were 97.92%, 98.75% and 98.13%, respectively (P> 0.05, LSD test). Based on the morphological characteristics, 18S rDNA and internal transcribed spacer (ITS) analysis, the isolates were identified to 61 taxa, of which Colletotrichum and Xylaria were the most dominant genera, and their relative frequencies were 40.00% and 23.68%, respectively. Only 21 taxa were common between bryophytes, pteridophytes and spermatophytes, whereas, some endophytes showed host specificity or tissue preference, for example, Penicillium chrysogenum and P. daleae were found only in bryophytes. In addition to Colletotrichum and Xylaria, Trichoderma and Penicillium were the dominant genera in bryophytes. However, in pteridophytes and spermatophytes, Phomopsis was the dominant genus. The Shannon indices (H′) and the Sorenson’s coefficient similarity indices (CS) of EF from bryophytes, pteridophytes and spermatophytes ranged from 2.02 to 2.92and 0.64 to 0.74, respectively. It was found that H′ of plants with different evolutional degree showed no significant difference (P> 0.05, LSD test). The CS of EF of two plant species with different evolutional degrees was not always lower than that of two plant species with the same evolutional degree.